Restructuring Qur'anic Education Centers to Enhance the Quality of Islamic Religious Education: A Strategic Framework - Dijan Novia Saka; Widya Sari; Agus Subandono; Muhammad Alfasa Ilham Haq; Amjad Ali Jokhio (LP2M Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2025)
This study analyzes the restructuring of the Qur'anic Education Institution in Indonesia as a strategy to improve the quality of Islamic religious education. While previous studies have discussed the effectiveness of learning methods, few have comprehensively examined the institutional restructuring, including administrative, pedagogical, and parental participation aspects. Therefore, this study fills this gap by presenting an integrated approach to restructuring Qur'anic Education Institution. This study employs a qualitative approach with a field research method. Data were collected through participatory observation, in-depth interviews, and documentation, then analyzed using the Miles and Huberman model: data reduction, data presentation, and conclusion drawing. The findings indicate that Qur'anic Education Institution faces various challenges such as limited teaching staff, non-standardized administration system, and low participation in training programs facilitated by Mabin. The novelty of this study lies in identifying and implementing a community-based restructuring model that enhances teacher competence, improves the administration system, and strengthens collaboration with parents. The restructuring of Qur'anic Education Institution contributes significantly to improving the quality of religious education through a more effective teaching system, professional institutional management, and active stakeholders involvement. Penelitian ini bertujuan untuk menganalisis restrukturisasi Lembaga Pendidikan Al-Qur’an di Indonesia sebagai strategi peningkatan mutu pendidikan agama Islam. Meskipun berbagai studi sebelumnya telah membahas efektivitas metode pembelajaran, namun belum banyak yang mengkaji secara komprehensif proses restrukturisasi kelembagaan yang mencakup aspek administratif, pedagogis, dan partisipasi orang tua. Oleh karena itu, studi ini mengisi kekosongan tersebut dengan menyajikan pendekatan terpadu dalam penataan Lembaga Pendidikan Al-Qur’an. Penelitian ini menggunakan pendekatan kualitatif dengan metode penelitian lapangan. Data dikumpulkan melalui observasi partisipatif, wawancara mendalam, dan studi dokumentasi, kemudian dianalisis menggunakan model Miles dan Huberman: reduksi data, penyajian data, serta penarikan kesimpulan. Temuan menunjukkan bahwa Lembaga Pendidikan Al-Qur’an menghadapi berbagai tantangan, seperti keterbatasan tenaga pendidik, sistem administrasi yang tidak terstandarisasi, dan rendahnya partisipasi dalam program pelatihan yang difasilitasi oleh Mabin. Kebaruan dari studi ini terletak pada identifikasi dan implementasi model restrukturisasi berbasis komunitas yang mencakup peningkatan kompetensi guru, pembenahan sistem administrasi, serta penguatan kolaborasi dengan orang tua. Restrukturisasi Lembaga Pendidikan Al-Qur’an berkontribusi signifikan terhadap peningkatan kualitas pendidikan agama melalui sistem pengajaran yang lebih efektif, manajemen kelembagaan yang profesional, dan keterlibatan aktif para pemangku kepentingan.